PENGAWETAN KAYU SUNGKAI (Peronema canescens jack) MEMAKAI DUA JENIS BAHAN PENGAWET - Sasa Abdurrohim (Pusat Penelitian dan Pengembangan Hasil Hutan, 1991)
Air dry sungkai (peronema canescens jack) wood samples, measuring 3 cm x 3 cm (432 samples) were treated with cold soaking treatment using wolmanit CB and Diffusol CB and diffusol CB preseruatibes for 1,2,3,4,5,6,7,8, and 9 daya at the concentrations of 2, 4, 6, and 8 %. The results show ot the construction sungkai timber used under the root without soil contact can be treated with both preservatives at the concentration of 6 and 8 %. the soaking duration for each concentration was 9 and 4 days respectively for wolmanit CB preservative, and 7 and 6 days for diffusol CB. For out door construction without soil contact, the timbers should be treated by 8 % diffusol CB by soaking duration of 9 days.